If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36=-2(y+6)
We move all terms to the left:
36-(-2(y+6))=0
We calculate terms in parentheses: -(-2(y+6)), so:We get rid of parentheses
-2(y+6)
We multiply parentheses
-2y-12
Back to the equation:
-(-2y-12)
2y+12+36=0
We add all the numbers together, and all the variables
2y+48=0
We move all terms containing y to the left, all other terms to the right
2y=-48
y=-48/2
y=-24
| -2=11-y÷3 | | 22=79-h | | -138+40k=22k+85k | | 15n+36=3 | | 79=22+8h | | 38-5n=2+n | | 79-22=8h | | 2x+28=44 | | H(d)=-5d^2+70d+65 | | 15n+3=36 | | 4(n+2)+2n+8=118 | | d=-5d^2+70d+65 | | 79=22h=8 | | 60b^2+6b+162=0 | | 7(x+3)-8=55 | | 9x+3=5x+7-4x | | 5n-15=2n+3015 | | 11x+3=6x+6 | | 4w+12=7w−13 | | 36/24=12/d | | z3− 1= 3 | | z/3− 1= 3 | | 6(v-3)=4(v-8) | | 8x^2+4x-9=0 | | 9k-6=5k+18 | | 1/2x-8.5=4 | | d=-5d^2+10d+120 | | 4(9+7x)=120 | | 4n+3n+8=92 | | -2=11-x÷3 | | F(x)=5^x-4+10 | | X2+18x+74=0 |